Comprehensive pan-cancer genomic landscape of KRAS altered cancers and real-world outcomes in solid tumors - Jessica K. Lee; Smruthy Sivakumar; Alexa B. Schrock; Russell Madison; David Fabrizio; Ole Gjoerup; Jeffrey S. Ross; Garrett M. Frampton; Pavel Napalkov; Meagan Montesion; Jennifer L. Schutzman; Xin Ye; et al. (npj Precision Oncology, 2022)
Abstract Recent clinical development of KRAS inhibitors has heightened interest in the genomic landscape of KRAS-altered cancers. We performed a pan-cancer analysis of KRAS-altered samples from 426,706 adult patients with solid or hematologic malignancies using comprehensive genomic profiling; additional analyses included 62,369 liquid biopsy and 7241 pediatric samples. 23% of adult pan-cancer samples had KRAS alterations; 88% were mutations, most commonly G12D/G12V/G12C/G13D/G12R, and prevalence was similar in liquid biopsies. Co-alteration landscapes were largely similar across KRAS mutations but distinct from KRAS wild-type, though differences were observed in some tumor types for tumor mutational burden, PD-L1 expression, microsatellite instability, and other mutational signatures. Prognosis of KRAS-mutant versus other genomic cohorts of lung, pancreatic, and colorectal cancer were assessed using a real-world clinicogenomic database. As specific KRAS inhibitors and combination therapeutic strategies are being developed, genomic profiling to understand co-alterations and other biomarkers that may modulate response to targeted or immunotherapies will be imperative.